2017
DOI: 10.1140/epja/i2017-12247-0
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduction of $\eta$ η mesons from the neutron: Cross sections and double polarization observable E

Abstract: Abstract. Results from measurements of the photoproduction of η mesons from quasifree protons and neutrons are summarized. The experiments were performed with the CBELSA/TAPS detector at the electron accelerator ELSA in Bonn using the η → 3π 0 → 6γ decay. A liquid deuterium target was used for the measurement of total cross sections and angular distributions. The results confirm earlier measurements from Bonn and the MAMI facility in Mainz about the existence of a narrow structure in the excitation function of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 74 publications
(187 reference statements)
1
7
0
Order By: Relevance
“…The magnitude and the energy and angular dependence of FSI can differ significantly between reactions. Previous experiments have shown that FSI for η photoproduction off deuterons in the energy range discussed here is negligible for cross sections and also for polarization observables [43,57,60,[74][75][76]. Also for photoproduction of η ′ mesons, no significant effects were observed [44].…”
Section: H Correction Of Final State Interaction Effectsmentioning
confidence: 53%
“…The magnitude and the energy and angular dependence of FSI can differ significantly between reactions. Previous experiments have shown that FSI for η photoproduction off deuterons in the energy range discussed here is negligible for cross sections and also for polarization observables [43,57,60,[74][75][76]. Also for photoproduction of η ′ mesons, no significant effects were observed [44].…”
Section: H Correction Of Final State Interaction Effectsmentioning
confidence: 53%
“…No significant effects were found for ππ and πη pairs. Also, for the helicity asymmetry E, as defined in this paper, no effects were found for single π 0 [37] and η production [33][34][35], although the effects on absolute cross sections for π 0 production are substantial. For πη production also shapes of invariant mass distributions of meson-meson and mesonnucleon pairs are basically unaffected [24].…”
Section: Complications For Quasi-free Production Off Bound Nucleonsmentioning
confidence: 65%
“…This observable allows the separation of the unpolarized cross section into the helicity-1/2 and helicity-3/2 parts. Results for η production became recently available [35][36][37] and this paper summarizes the first results for this observable for single π 0 production off the neutron.…”
Section: Introductionmentioning
confidence: 98%